Decomposition analysis of oil export dependency: a case study of Mexico, Indonesia and Nigeria. Issue 1 (2nd January 2016) - Emodi, Nnaemeka Vincent; Boo, Kyung-Jin
Abstract: This paper investigated the oil export dependency of Mexico, Indonesia and Nigeria, which are major oil-producing countries in their respective geographical regions, and how their oil export have evolved over the last two decades. Oil export importance was analysed by relating it to the effective export price, oil export importance, oil dependence and energy intensity of Mexico, Indonesia and Nigeria for the period 1986–2010. The trends were analysed for Mexico, Indonesia and Nigeria, while the decomposition result showed that price effect had the most influential factors to revenue changes in the three countries. Indonesia and Nigeria were less oil export intensive in the last period, 2001–2010, and the three countries had an improvement in their energy efficiency due to a decrease in energy intensity. The authors recommend that energy efficiency improvements and reduction in oil export dependence, with the diversification of export will improve the country's revenue and safeguard their economies against decline in oil prices.